Implementation of Literacy Learning for Students in Increasing Interest in Reading in The Matja Bhaca Community - Inayati, Putri Nur; Arbarini, Mintarsih; Shofwan, Imam (Lembaran Ilmu Kependidikan, 2024)
A culture of literacy can provide direction and guidance to realize a broad- minded society. The Matja Bhaca community is a forum for the younger generation and the community to work together to foster a culture of literacy and develop interest in reading in Majalangu Village and its surroundings. The focus of this community is to create a society that loves to read, be creative and can work to advance literacy in Indonesia. The purpose of the study was to describe the implementation of literacy learning and the obstacles and solutions to literacy learning for students in the Matja Bhaca Community. This research is a qualitative research. The subjects of the research were students in Matja Bhaca Community. The location used as a research site, namely the Matja Bhaca Community, Majalangu Village, Watukumpul District, Pemalang Regency. The collection technique was carried out using observation, interview, and documentation techniques. Data validity techniques used in this research are source triangulation and technique triangulation techniques. The results of this study show that the implementation of literacy learning has an impact on improving the reading, writing and public speaking skills of students in the Matja Bhaca Community. Learners can communicate well, are more confident to display their work both orally and in writing. The obstacles in the implementation of literacy learning in reading, writing and public speaking at Matja Bhaca Community are difficult learning schedule adjustments, literacy still seems unpleasant for students, changing attitudes of students, and inadequate facilities and infrastructure. Solutions that can be used include planning a flexible learning schedule, always involving participants in choosing materials or topics, providing emotional support and teaching concentration management, creating intensive but effective learning sessions, and mobilizing support from related parties to improve learning facilities.